EXPLORING THE INFLUENCE OF CONSUMER BEHAVIOR ON PURCHASE DECISION AND PURCHASE INTENTION FOR HALAL COSMETICS: THE MODERATING ROLE OF HALAL AWARENESS - Khanfani, Mohammad; Diniyah, Afrohiyatid; Putri, Ghaitsa Zahira Ardelia (Airlangga International Journal of Islamic Economics and Finance, 2023)
In recent years, Halal product demand has increased, boosting the global economy. Indonesia has the world's largest Muslim population, and its Halal cosmetics sector is strongly tied to customer purchasing decisions based on purchase intentions and loyalty as post-purchase behaviors. Halal products need marketing techniques as new ones are introduced. This research examines how halal product certification, brand awareness, brand image, and customer loyalty affect consumer purchasing decisions for halal cosmetics. Indonesian halal cosmetics were studied. A survey of 66 East Java Muslim residents provided data. This study found that customer loyalty, halal awareness, and purchase intention influence purchasing intention. Halal Certification, Price, and Brand Image are insignificant. Halal awareness, a moderating influence of purchasing intention on purchase decisions, has no significant effect.